Systematics of interstitial encrusting bryozoans from southeastern Brazil - Winston, Judith E.; Vieira, Leandro M. (Zootaxa, 2013)
This paper describes 22 species of marine bryozoans found in the sand-grain-encrusting interstitial epifauna of the northeast coast of São Paulo state, Brazil: one new cyclostome, Disporella calcitrapa sp. nov., and 21 cheilostomes. Sixteen of the cheilostomes are new species, and three represent new genera. They are Ammatophora arenacea sp. nov., Discoporella gemmulifera sp. nov., Puellina caraguata sp. nov., Puellina tuba sp. nov., Rosulapelta rosetta gen. et sp. nov., Collarina spicata sp. nov., Hippothoa calcicola sp. nov., Trypostega ilhabelae sp. nov., Reptadeonella granulosa sp. nov., Drepanophora irregularis sp. nov., Allotherenia sabulosa gen. et sp. nov., Bryopesanser tilbrooki sp. nov., Psammocleidochasma tridentatum gen. et sp. nov., Celleporina abstrusa sp. nov., Hippoporella castellana sp. nov., and Hippoporella sabulonis sp. nov. Other species found in this habitat, Alderina smitti, Cymulopora uniserialis, Vibracellina laxibasis, Akatopora leucocypha, and Smittipora sawayai, have previously been described. The family Cymuloporidae fam. nov. is erected for Cymulopora and Crepis. The occurrence in this habitat of living colonies of bryozoans more characteristic of larger subtidal shell substrata indicates the potential importance of an interstitial refuge in maintaining and dispersing encrusting bryozoan populations along continental shelves where larger substrata are absent or rare.